Flipped Learning and Digital Competence: Techno-Pedagogical Design and University Students Perception - Alberto Dafonte Gómez; Oswaldo García Crespo; Diana Ramahi García (Index Comunicación, 2018)
This article documents the application of a techno-pedagogical design based on the TPCK (Technological Pedagogical Content Knowledge) model of technology integration in teaching and in flipped learning, in a subject of the Degree in Advertising and Public Relations of the University do Vigo and analyzes the level of engagement and satisfaction of students with the implementation. To measure students' perceptions, a voluntary questionnaire administered before the end of the semester was used for the accidental sample composed of those enrolled in the subject (60 responses); the data obtained were analyzed and then confronted with the assessments received in the Survey of Teaching Evaluation, administered by the university to the same sample by an external company. The data provided by this institutional survey also allow a longitudinal comparison with the results obtained in previous courses in which different teaching methodology was used. The results show the high level of engagement, satisfaction and assessment by the students of the teaching approach used and it is concluded that the teaching methodology based on flipped learning and the cross-cutting integration of technology is considered by the participants as very satisfactory and useful in their learning process.